Post road traffic accident one-month old, extra-large heel defect coverage by delayed reverse sural artery flap: an interesting case report - Gupta, Madhusoodan; Varshney, Deepti; Biswkarma, Vishal K. (International Surgery Journal, 2021)
Post road traffic accident (RTA) complete heel avulsion injury is not very common, but once it happened, it is very challenging to plastic and reconstructive surgeon to reconstruct the total heal avulsion defect. There is paucity of soft tissue in the region of foot, ankle and lower one third of leg. Although the micro vascular free flap reconstruction is gold standard for reconstruction of large heel defect but not feasible most of the time. Reverse sural artery flap (RSAF) is a workhorse flap for reconstruction of heel and lower 1/3rd leg defect. Here we reported a case of 28 years old young man, who had road traffic accident and sustained complete right heel avulsion injury with calcaneal and right tibia bone fracture. Patient was presented to author one month later after the injury with extra-large infective right heel defect size 15×12 cm with k-wires in exposed calcaneal bone. Patient’s surgery was done in two stages. Delayed RSAF survived completely and well settled in our case.